Pengaruh Budaya Organisasi Terhadap Disiplin Kerja Karyawan PT. Timur Jaya Pekanbaru - Wicara, Dinda Genta (Sekolah Tinggi Ilmu Ekonomi Riau, 2022)
The purpose of this study is to determine the influence of organizational culture on employee work discipline at PT Timur Jaya Pekanbaru. To achieve this goal, a study was conducted using a sample of 35 people, using a random census method. Methods of data analysis using simple linear regression. Based on the results of testing organizational culture has a significant effect on Employee Discipline of PT Timur Jaya Pekanbaru, this is proven based on the t test found that t-count is greater than t-table (3.829 > 2.034). R. Square value of 0.308. This means that the contribution or contribution of organizational culture to the work discipline of employees of PT Timur Jaya Pekanbaru is 30.80% while the remaining 69.20% is influenced by other variables outside of organizational culture variables. Recommendations that can be submitted It is hoped that employees will further improve their work culture by carrying out all work according to applicable guidelines.